Effect of Hanging White Bedsheet Around Phototherapy Unit on TSB Level in Neonatal Jaundice: A Comparative Study - Chong, Li Tsu; Lee, Shalin Wan Fei; Chan, Kim Geok; Saloma, Pawi; Feryante, Rintika; Drina, Dalie (UPM Press, 2020)
Introduction: Phototherapy is the primary treatment for neonatal jaundice and is evaluated via total serum bilirubin (TSB) level. Hanging white material around phototherapy unit can multiply energy delivery by many folds. This study is to evaluate the effect of hanging white bedsheet around phototherapy unit on the reduction of TSB level. Methods: Comparative interventional study was conducted in two public hospitals. 200 eligible neonates with hyperbilirubinemia were recruited and assigned to intervention (n=100) and control group (n=100). Neonates assigned into intervention group were nursed under phototherapy with the addition of white bedsheet hanging around the unit while the control group were nursed under phototherapy with non-white curtains. Results: Mothers’ blood group (x = 3.75, p = .29), neonates’ blood group (x = 2.87, p = .41), birth weight (t = 1.41, p = .16), baseline total serum bilirubin (TSB) level (p = .08), baseline irradiance of phototherapy prior to the hanging of curtains (p = .13) and hours of phototherapy (p = .53). The mean for TSB level in intervention and control group at 24 hours was 235.82µmol/L and 208.67µmol/L respectively. The mean difference in TSB level between intervention and control group was statistically significant at 24 hours (x = 27.15, t = 4.56, p < .001) and 48 hours (x = 19.27, t = 2.32, p = .02) after initiation of phototherapy. Conclusion: The baseline and demographic characteristics of the neonates and mothers were comparable between the intervention and control group. The TSB level at 24 hours and 48 hours were significantly lower in control group if compared to the intervention group. Therefore, hanging white bedsheet did not significantly hasten the reduction of TSB level when compared to ordinary non-white curtains.